PROFIL KEMAMPUAN MAHASISWA BIOLOGI DALAM MEMBUAT LKS IPA JENJANG SMP - Arinta Winsi; Pramudiyanti Pramudiyanti; Berti Yolida (Universitas Lampung, 2014)
This research aimed to know the Biology Education of Lampung University student’s profile in composing science worksheet for junior high school. The design was simple descriptive by purposive sampling so those 19 students participated in PPL year 2013 who composed science worksheet were choosen as subject. The qualitative data were obtained from score conversion in assessment result, questionnaire, and competencies test. The assessment result showed that students had a good composing skill reviewed from format (79.91) and content (62.93) aspect. From format aspect, was categorized passable (60.09) in structure and was categorized very good both in readability and attractivity (93.68 and 85.97). From content aspect, was categorized passable (42.10 and 53.50) in composing basic and advanced Science Process Skill then was categorized good (71.93) in composing activities appropriately to Basic Competence and Lesson Plan. The student’s understanding of composing worksheet based on the both of rules was categorized passable (59.17 and 60). Penelitian ini bertujuan untuk mengetahui profil mahasiswa Pendidikan Biologi Universitas Lampung dalam menyusun LKS IPA jenjang SMP. Desain yang digunakan adalah deskriptif sederhana dengan purposive sampling sehingga 19 orang mahasiswa peserta PPL tahun 2013 yang membuat LKS diambil sebagai subjek. Data kualitatif didapat dari konversi skor penilaian LKS, angket, dan uji kompetensi. Hasil penilaian menunjukan mahasiswa berkemampuan baik dalam membuat LKS IPA ditinjau dari segi format (79,91) dan isi (62,93). Dari segi format, berkategori cukup (60,09) pada susunan serta berkategori sangat baik pada keterbacaan dan kemenarikan (93,68 dan 85,97). Dari segi isi, berkategori cukup (42,10 dan 53,50) dalam menyusun muatan Keterampilan Proses Sains dasar dan lanjut serta berkategori baik (71,93) dalam menyusun kegiatan yang sesuai dengan KD dan RPP. Pemahaman mahasiswa mengenai penyusunan LKS sesuai kaidah berkategori cukup (59,17 dan 60). Kata kunci : kemampuan, LKS IPA, mahasiswa pendidikan biologi